The private healthcare setting as a place for educating nurses: A qualitative exploration. (2022) - Meyer, Rhoda; Archer, Elize; Van Schalkwyk, Susan C.
Abstract: Background: Understanding the learning environment is necessary for the development and implementation of effective curricula, including that of nursing education. The nursing education context has been undergoing various shifts, specifically in response to the need to scale up the number of healthcare professionals. These shifts have resulted in various transitions both in terms of the site of learning, such as the private healthcare environment, as well as the nature of its programme offerings. Objective: To explore nursing students' perceptions of the private healthcare context as an environment for learning. Methods: A qualitative interpretative case study was undertaken to gain insight into a very specific learning environment. The population included bridging course nursing students undertaking their training at a private higher education institution (R683). Purposive sampling was used, and data were collected by means of focus group discussions. Data analysis was organised according to a three-tiered analytical ladder. Results: The findings point to two key issues: there was variability in how the students experienced the private healthcare setting as a place for learning, and this experience was influenced by a number of tensions within this environment. Conclusion: Curriculum developers should explore ways of optimising these contextual variations into the curriculum so that students can maximise the benefits of these diverse learning experiences. Educators should nurture the skills of adaptability in students so that they learn to cope with the complexities of these environments. Furthermore, the students' role in their own learning as well as co-constructing the learning environment should also be emphasised.